Selection of pasture legumes tolerant to aluminium and efficient in phosphorus uptake. II. Exotic legumes. - Milan, Paulo Anisio; Ritter, Wolfgang; Dall'agnol, Miguel (Pesquisa Agropecuaria Brasileira, 2014)
Twelve legumes were grown in a glasshouse pot trial at two lime levels (3,5 and 10,5 t/ha) and two phosphate treatments (66 and 198 mg of P/pot) to study their Al tolerance and their efficiency of P uptake. Various annual and perennial species of the genera Trifolium, Lotus and Ornithopus were tested, utilizing a "Vacaria" soil (Haplohumox) high in exchangeable Al, low in P and very acid. Within the perennial group, Lotus uliginosus tolerated low pH and utilized P efficiently, whilst Trifolium pratense was only efficient in P utilization. The various Ornithopus species in the annual group did not respond to increased soil pH. Ornithopus sativus 4700, O. compressus 4420, O. compressus 4301 and O. isthmocarpus 4425 were the most efficient in P uptake